Application of meta‐ and para‐Phenylenediamine as Enhanced Oxime Ligation Catalysts for Protein Labeling, PEGylation, Immobilization, and Release. (2nd February 2015) - Mahmoodi, Mohammad M.; Rashidian, Mohammad; Zhang, Yi; Distefano, Mark D.
Abstract: Meta‐ and para‐ phenylenediamines have recently been shown to catalyze oxime and hydrazone ligation reactions at rates much faster than aniline, a commonly used catalyst. Here, we demonstrate how these new catalysts can be used in a generally applicable procedure for fluorescent labeling, PEGylation, immobilization, and release of aldehyde‐ and ketone‐ functionalized proteins. The chemical orthogonality of phenylenediamine‐catalyzed oxime ligation versus copper‐catalyzed click reaction has also been harnessed for simultaneous dual labeling of bifunctional proteins containing both aldehyde and alkyne groups in high yield. © 2015 by John Wiley & Sons, Inc.